RP-HPLC Method for Simultaneous Determination of Valsartan and Fenofibrate from PPI Dendrimer - Sureshkumar, P.; Vijaya Ratna, J.; Hematheerthani, N. (Asian Journal of Chemistry, 2013)
The present study aimed at synthesizing PPI dendrimer and loading dual drug followed by developing stability indicating reversed-phase HPLC method and subsequent validation for simultaneous estimation of valsartan and fenofibrate. The proposed RP-HPLC method utilizes a Nucleosil 100, 5 μm, C8, 250 × 4.0 mm column, mobile phase consisting of methanol : 1 % orthophosphoric acid : acetonitrile (45:30:25) and UV detection at 247 nm. The described method was linear over a range of 10-50 μg/mL for valsartan and 3-15 μg/mL for fenofibrate. The mean recoveries were 99.91 and 100.53 % for valsartan and fenofibrate, respectively. Statistical data's were used to check the intermediate precision data obtained under different experimental setups. The calculated value was found to be less than critical value.